2023
DOI: 10.1021/acsami.3c04390
|View full text |Cite
|
Sign up to set email alerts
|

Quaternary Pullulan-Functionalized 2D MoS2 Glycosheets: A Potent Bactericidal Nanoplatform for Efficient Wound Disinfection and Healing

Abstract: Rapid emergence of multidrug-resistant bacterial strains has posed a global threat to public health. Hospital-acquired infections, especially in diabetic and burn patients, severely impede the process of wound healing, thereby causing high mortality. This calls for developing a new biomaterial that synergistically destroys pathogenic strains and also helps in promoting wound healing without causing any resistance generation. A new and highly potent antibacterial agent has been developed by integrating the bact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 69 publications
0
7
0
Order By: Relevance
“…In our previous study, 25 we reported the highly efficient antibacterial and wound healing efficiency of MCP glycosheets against both Gram-positive and Gram-negative bacteria through a combined action of the individual antibacterial properties of MoS 2 nanosheets and CP polysaccharide. In this study, we further exploited this property of MCP glycosheets to fabricate antibacterial coatings for medical implants.…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…In our previous study, 25 we reported the highly efficient antibacterial and wound healing efficiency of MCP glycosheets against both Gram-positive and Gram-negative bacteria through a combined action of the individual antibacterial properties of MoS 2 nanosheets and CP polysaccharide. In this study, we further exploited this property of MCP glycosheets to fabricate antibacterial coatings for medical implants.…”
Section: Resultsmentioning
confidence: 95%
“…To begin with, the fabrication of MCP glycosheet coated substrates, positively charged MCP glycosheets were first synthesized in a one-step process of ultrasonication assisted exfoliation of MoS 2 using cationic polysaccharide, CP, as both exfoliating and functionalizing agent, as reported in our previous study. 25 These cationic MCP glycosheets are decorated with quaternary amine and hydroxyl groups on its surface, which help in their attachment to the surface of SS and PVF substrates using polydopamine as an anchorage layer. The SS and PVF substrates were dipped in dopamine solution for a specific time to deposit a thin layer of polydopamine (PDA) on the surface of these substrates.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Dextrin was initially cationized by incorporating quaternary ammonium groups onto the polymeric backbone using GTMAC following a process reported earlier. 31,35,36 Cyt C was suspended in an alkaline buffer of pH 11, higher than its pI (10.8), which made the suspended protein negatively charged. The protein suspension (500 μg) was allowed to stir along with the polymer cationic dextrin (CD) at a concentration of 0.5 mg mL −1 for 30 min to interact electrostatically with each other.…”
Section: Methodsmentioning
confidence: 99%
“…For 2D MoS 2 sheets, they have a large surface area and can be easily functionalized. 63 This makes them effective in inhibiting bacterial growth. They are also versatile and can be incorporated into various materials.…”
Section: The Structure Synthesis and Characteristics Of Mos2mentioning
confidence: 99%